The Effect of Training and Competency on Employee Performance Through Employee Engagement as a Mediating Variable at the Tugu Canggu Hotel, Bali - Ayu Suryawati; Surya Nugraha (Universitas Triatma Mulya, 2024)
This research aims to investigate the impact of training and competency on employee performance, with employee engagement serving as a mediating factor at the Tugu Bali Hotel. The study's population consists of 103 employees of the Tugu Bali Hotel, selected using the probability sampling method. Path analysis was employed to test the research hypotheses. The findings reveal that: 1) Training has a positive and significant impact on employee engagement at the Tugu Bali Hotel; 2) Competency has a positive and significant effect on employee engagement at the Tugu Bali Hotel; 3) Training positively and significantly affects employee performance at the Tugu Bali Hotel; 4) Competency positively influences employee performance at the Tugu Bali Hotel; 5) Employee engagement positively affects employee performance at the Tugu Bali Hotel; 6) Employee engagement serves as a mediating variable in the relationship between training and employee performance at the Tugu Bali Hotel; and 7) Employee engagement acts as a mediating variable in the connection between competency and employee performance at the Tugu Bali Hotel. Based on these findings, it is recommended that the management of the Tugu Bali Hotel focus on enhancing employee training, competency, and engagement to boost overall employee performance.